Business Strategic During Pandemic for DO IT Chocolate - University of Pamulang - Lely Suryani; Sasmita Sari Ardaninggar; Asih Handayani (Universitas Islam Bandung, 2023)
It has been almost two years since the Covid-19 virus pandemic has impacted health, education, social life, culture, and economy. One of the supporting sectors of the nation's economy that has been dramatically affected by the COVID-19 pandemic is the Micro, Small and Medium Enterprises (UMKM) sector, one of which is DO IT Chocolate, where chocolate tours are usually held, which had to be abolished and then reduced income from gift shops and tourist attractions. The purpose of this paper is the DO IT chocolate management strategy to bounce back during the Covid-19 era. From the results of this study, it was carried out that to maintain the continuity of DO IT Chocolate, and various strategies were carried out, ranging from determining market segments, product certification to increase consumer confidence, innovating, always paying attention to product quality, promotions, utilizing digital marketing, networking, venturing into traders. and export is a very appropriate strategy during the covid-19 pandemic